Complex carbonate-sulfate brines in fluid inclusions from carbonatites: Estimating compositions in the system H2O-Na-K-CO3-SO4-Cl. (15th May 2020) - Walter, Benjamin F.; Steele-MacInnis, Matthew; Giebel, R. Johannes; Marks, Michael A.W.; Markl, Gregor
Highlights: Fluid inclusion data from carbonatite. A new approach for quantification. Exsolution of (Na, K)Cl + (Na, K)2 CO3 + (Na, K)2 SO4 fluids with salinities up ∼80 wt.% Fluid boiling as trigger for apatite crystalization. Abstract: Studies of fluid inclusions in carbonatitic rocks are essential for understanding physicochemical processes involved in carbonatite-related hydrothermal ore mineralization and fenitization. However, the composition of many carbonatite-derived fluids is challenging to quantify, which hampers their detailed interpretation. Here, we present a systematic study of microthermometry of fluid inclusions found in carbonatites from the Kaiserstuhl (SW Germany), and a simple numerical model to estimate the compositions of such fluids, which are typical of numerous carbonatites worldwide. Four types of fluid inclusions have been identified in the Kaiserstuhl carbonatites: (I) vapor-poor H2 O-NaCl fluids with <50 wt.% salinity; (II) vapor-rich H2 O-NaCl-CO2 fluids with <5 wt.% salinity; (III) multi-component fluids with high salinity and high CO2 contents; and (IV) multi-component fluids with high salinity but little to no CO2 . At present, it is only possible to quantify fluid compositions for types I and II. For the complex types III and IV, we conducted predictive modeling of the liquidus surface based on the Margules equations. The results suggest that carbonatite melts predominantly exsolve Na-K-sulfate-carbonate/bicarbonate-chloride brines (types III or IV). Such fluid inclusions may represent immiscible fluids that were trapped after segregation by boiling from a parental highly saline brine (type I). Fluid boiling, in turn, was probably triggered by a rapid pressure release during melt ascent. The present model enables quantification of fluid compositions associated with carbonatitic magmatism.